Multiple sclerosis and HLA genotypes: A possible influence on brain atrophy. (January 2019) - Lorefice, Lorena; Fenu, Giuseppe; Sardu, Claudia; Frau, Jessica; Coghe, Giancarlo; Costa, Gianna; Schirru, Lucia; Secci, Maria Antonietta; Sechi, Vincenzo; Barracciu, Maria Antonietta; Marrosu, Maria Giovanna; Cocco, Eleonora
Background: The strongest genetic determinant for multiple sclerosis (MS) is located at the human leukocyte antigen (HLA) class II DRB1 and DQB1 loci. Objectives: To investigate the possible role of predisposing HLA genotypes in determining brain atrophy. Methods: HLA genotypes were categorized as high risk (two predisposing haplotypes) or medium/low risk (one or no predisposing haplotypes). Patients underwent a brain magnetic resonance imaging (MRI) study and volumes of white matter (WM), gray matter (GM), and whole brain (WB) were estimated with SIENAX. Longitudinal atrophy was also assessed with SIENA. Results: The study included 240 MS patients. In 51/240 (21%) subjects, a high-risk HLA genotype was observed, while medium- and low-risk HLA genotypes were 109/240 (45%) and 80/240 (34%), respectively. Multiple regression analysis found that the high-risk HLA genotype was associated with significant reduction in WB ( p  = 0.02) and GM ( p  = 0.03) volumes compared with the medium-/low-risk HLA genotypes, independently from MS clinical features. The longitudinal study included 60 patients and showed a brain volume loss of −0.79% in high-risk HLA genotype group versus −0.56% in low-risk HLA genotype. Conclusion: Our results suggest an influence of HLA genotype on WB and GM atrophy. Further investigations are necessary to confirm these findings.